STUDI PENDAHULUAN TENTANG PENERAPAN METODE AMBANG BERTINGKAT UNTUK ANALISIS KEKERINGAN HIDROLOGI PADA 15 DAS DI WILAYAH JAWA TIMUR - Indarto Indarto; Sri Wahyuningsih; Muhardjo Pudjojono; Hamid Ahmad; Ahmad Yusron (JURNAL AGROTEKNOLOGI, 2014)
This research deals with identification of potential hydrological drought at 15 watersheds in Eastern part of East Java Province. Hydrological drought events is indicated by water deficits at the main river of the watersheds during certain period of record. Discharge data from 15 watersheds in East Java are used as main input for this analysis. TLM modul based on HydroOffice platform is used to calculate the deficit. Deficit event is counted when the discharge during more than > 7 days is below the threshold level. The threshold level is set up using percentile 90% (Q90). The value of Q90 is determined from discharge times series. Furthermore, the discharge is rangked from high to low flow. Results from TLM are then imported to EXCEL for further analysis. Furthermore, GIS software package (Quantum GIS) is used for mapping the spatial variation of discharge values (avarage, maximum, Q90), frequency and duration of deficits events. This analysis produces the spatial maps of discharge value and deficit events ( averaged annually).Keywords: TLM, hydrological drougth, percentile 90 (Q90), discharge